Characterization of (Mg1.0Zn0.0)TiO3+4 wt%Bi2O3 Ceramics for Application as Resonator in Dielectric Resonator Oscillator Circuit - Izza, Lailatul; Ermawati, Frida Ulfah (Universitas Andalas, 2021)
MgTiO3-based ceramics have potential applications in telecommunications systems at microwave frequencies, such as resonators in dielectric resonator oscillator (DRO) circuits. This paper reports the results of (Mg1.0Zn0.0)TiO3+4wt% Bi2O3 (abbreviated MZT0+4wt%Bi2O3) ceramic fabrication to assess its potential to be used as a resonator in the DRO circuit. We characterized its structure, microstructure, and bulk density. The addition of 4wt%Bi2O3 to MZT0 crystalline powder was carried out via ball-mill. The milled powder was compacted using a die press to obtain pellets. All pellets were sintered at 1100ºC for 4, 6, and 8 h. Ceramic structures of the 4 and 6 h holding time consists of MgTiO3 phase (94.33±2.68) and (95.34±1.95)% molar respectively, while the rest phase was TiO2. The 8-h ceramic structure comprises (96.11±2.94) % molar MgTiO3 accompanied by Mg2TiO5 and TiO2. The ceramics' microstructure consists of a cluster of grains with an average diameter of 1.32-2.24 μm and pores. Bulk density decreases with the increase of sintering holding time. The DRO characterization records a resonance signal each at 5.207, 5.005, and 5.121GHz with power approaching 0 dBm, suggesting that the MZT0+4wt%Bi2O3 ceramics can be used as a resonator in the DRO circuit working in microwave frequencies, especially at 5.0-5.2GHz.